An Overview of Early Anthrax Outbreaks in Northern Canada: Field Reports of the Health of Animals Branch, Agriculture Canada, 1962-71 - Dragon, D.C.; Elkin, B.T. (ARCTIC, 2001)
Between 1962 and 1971, six outbreaks of anthrax occurred in the bison herds of the Northwest Territories and northern Alberta. In response, the federal Health of Animals Branch dispatched staff veterinarians to oversee carcass disposal operations and later to take part in bison depopulation and vaccination programs. Recently, a collection of documents from that agency concerning the outbreaks was discovered in the federal archives. The collection includes field reports from the veterinarians that provide valuable, detailed, first-person accounts of the outbreaks and later programs, information which has generally been lacking in the published literature. The reports identify at least 1102 bison that died of anthrax during the six outbreaks, dozens more than reported previously. They also indicate that the disease spread into Wood Buffalo National Park in 1963, rather than in 1964, as reported previously. A minimum of 598 healthy bison were also killed in depopulation programs aimed at preventing the spread of anthrax into the Park, even though anthrax carcasses had already been discovered within the Park and the targeted regions would be repopulated within weeks. Coverage and revaccination rates were low throughout the vaccination program, and a further 828 bison died during the vaccine roundups. Entre 1962 et 1971, six épidémies d'anthrax ont eu lieu dans les troupeaux de bisons des Territoires du Nord-Ouest et de l'Alberta septentrional. La Direction générale de l'hygiène vétérinaire du gouvernement fédéral réagit en dépêchant ses vétérinaires attitrés pour superviser les opérations d'élimination des cadavres et pour participer ensuite aux programmes d'abattage intégral et de vaccination. On a découvert récemment dans les archives fédérales un ensemble de documents provenant de cette agence concernant les épidémies. Cette collection comprend des rapports d'enquête rédigés par les vétérinaires, qui offrent des récits à la première personne, intéressants et détaillés, sur les épidémies d' anthrax et les ...